Application of niclosamide and analogs as small molecule inhibitors of Zika virus and SARS-CoV-2 infection. (15th May 2021) - Shamim, Khalida; Xu, Miao; Hu, Xin; Lee, Emily M; Lu, Xiao; Huang, Ruili; Shah, Pranav; Xu, Xin; Chen, Catherine Z.; Shen, Min; Guo, Hui; Chen, Lu; et al.
Graphical abstract: Abstract: Zika virus has emerged as a potential threat to human health globally. A previous drug repurposing screen identified the approved anthelminthic drug niclosamide as a small molecule inhibitor of Zika virus infection. However, as antihelminthic drugs are generally designed to have low absorption when dosed orally, the very limited bioavailability of niclosamide will likely hinder its potential direct repurposing as an antiviral medication. Here, we conducted SAR studies focusing on the anilide and salicylic acid regions of niclosamide to improve physicochemical properties such as microsomal metabolic stability, permeability and solubility. We found that the 5-bromo substitution in the salicylic acid region retains potency while providing better drug-like properties. Other modifications in the anilide region with 2′-OMe and 2′-H substitutions were also advantageous. We found that the 4′-NO2 substituent can be replaced with a 4′-CN or 4′-CF3 substituents. Together, these modifications provide a basis for optimizing the structure of niclosamide to improve systemic exposure for application of niclosamide analogs as drug lead candidates for treating Zika and other viral infections. Indeed, key analogs were also able to rescue cells from the cytopathic effect of SARS-CoV-2 infection, indicating relevance for therapeutic strategies targeting the COVID-19 pandemic.